THE IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS IN CHILDCARE CENTRES (TASKA): ADDRESSING THE ASPIRATIONS OF MODERN PARENTS - NUR SARAH AIREEN MOHD IZZANI; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This library review examines practices of teaching and learning employed in childcare centres (TASKA) in Malaysia for infants and toddlers, with particular attention given to how they align with expectations of today's parents. Drawing on recent empirical evidence, policy analysis, and parents' perceptions, this study considers issues such as play-based learning, assessment practice, policy awareness, and quality of care. Major findings are that while numerous TASKA and ECCE schemes have adopted holistic and play-based pedagogies, significant gaps in the qualifications of teachers, parental awareness of policy, and educational quality consistency exist. The report concludes with policy suggestions for enhancement, teacher education, and stronger parent-centre partnerships to ensure early childhood care that meets the developmental needs of the child as well as the needs of parents.